(untitled) (Conferencea, 2022)
In this article, reforms to be carried out in the field of medicine after independence, changes in the quality and number of polyclinics over the past 10 years, funds allocated to the medical field from the state and their practical results, polyclinics currently existing in navoi region, qvp, the number of nurses and doctors, changes in the field of regional and interdistrict medicine, the increase in the number of medical institutions, and the improvement of the quality of medical services to the population are given complete information.